2016
DOI: 10.1016/j.jss.2015.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative consent for patients with limited English proficiency

Abstract: Background Informed consent is important for limited English proficient (LEP) patients undergoing surgery, as many surgical procedures are complicated, making patient comprehension difficult even without language barriers. The study objectives were to (1) understand surgeons’ preoperative consenting process with LEP patients, (2) examine how surgeons self assess their non-English language proficiency levels using a standardized scale, and (3) identify the relationship between self assessed non-English language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…17,18 While federal guidelines mandate the use of qualified interpreters for patients with LEP, 19 this is an unfunded mandate, and multiple studies have demonstrated low rates of professional interpreter utilization during hospital encounters, including during informed consent discussions. [20][21][22][23][24][25][26] Time constraints and lack of immediate availability have been implicated by clinicians as major barriers to use of professional interpreters in the hospital. 27 A recent study demonstrated that surgeons' decisions to use professional interpreters for informed consent discussions depended in large part on the rapid availability of interpreter services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 While federal guidelines mandate the use of qualified interpreters for patients with LEP, 19 this is an unfunded mandate, and multiple studies have demonstrated low rates of professional interpreter utilization during hospital encounters, including during informed consent discussions. [20][21][22][23][24][25][26] Time constraints and lack of immediate availability have been implicated by clinicians as major barriers to use of professional interpreters in the hospital. 27 A recent study demonstrated that surgeons' decisions to use professional interpreters for informed consent discussions depended in large part on the rapid availability of interpreter services.…”
mentioning
confidence: 99%
“…27 A recent study demonstrated that surgeons' decisions to use professional interpreters for informed consent discussions depended in large part on the rapid availability of interpreter services. 21 Best practices to overcome these barriers remain unclear; however, it stands to reason that convenient and rapid access to professional interpreter services could be effective. 28 A previous pilot study to increase easy access to professional interpreters demonstrated a substantial increase in professional interpreter utilization via interpreter phones, without a decrement in inperson professional interpreter utilization.…”
mentioning
confidence: 99%
“…Special attention to patients with additional risk for marginalization, such as non-English speaking patients, is necessary to ensure that autonomy is not substituted with provider convenience. 20 In our study, patients with lower socioeconomic status and education levels were less likely to provide surgical consent. Health literacy is an area of concern for older adults, with one study citing 22.7% of patients with normal cognitive function and 40.8% of patients with mild cognitive impairment having inadequate health literacy.…”
Section: Discussionmentioning
confidence: 60%
“…A patient's English proficiency may be judged sufficient for consent. Ease of access to professional interpretation is an important facilitator of its use, and surgeons report using ad hoc interpretation if wait times for professional interpretation are greater than 15 min 8 …”
Section: Discussionmentioning
confidence: 99%
“…Ease of access to professional interpretation is an important facilitator of its use, and surgeons report using ad hoc interpretation if wait times for professional interpretation are greater than 15 min. 8 Many institutions, like ours, have policies requiring the use of professional interpretation for informed consent. However, policies are weak levers in motivating change.…”
Section: Discussionmentioning
confidence: 99%